ZOOPLANKTON - Serafim Junior, Moacyr (2014)
The spatial and temporal variation of the zooplankton was studied over an annual cycle at three collection points along the reservoir in the fluvial, transition and lacustrine regions. Altogether, 63 zooplankton species were identified, with 40 Rotifera, 15 Cladocera, and eight Copepoda. Among the Rotifera, 23 species were considered to be rare (< 25%), 11 were considered as frequent (25-75%), and seven as constant (> 75%). Regarding the Cladocera, seven species were considered rare, seven frequent, and just one was considered as constant. One Copepoda species was considered rare, four were frequent, and three constant. An increase in diversity of the zooplankton groups was found during the spring and summer months. The most abundant Rotifera species were: Conochilus unicornis, Kellicotia bostoniensis, and Polyarthra vulgaris, all above 18,000ind.m(-3). Among the Cladocera, Bosmina hagmanni was the most abundant species, with an average value of 20,313ind.m(-3), followed by Ceriodaphnia cornuta var. rigaudi with 3,912ind.m(-3). Among the Copepoda, nauplii of Cyclopoid prevailed, with an average value of 47,756ind.m(-3). For adults, higher abundances (above 1,300ind.m(-3)) were observed for Thermocyclops minutus, Thermocyclops decipiens, and Microcyclops anceps; for Calanoida, Notodiaptomus spiniger was the most abundant. The richness of species of zooplankton found in the present study was consistent with that expected for oligo-mesotrophic reservoirs.